Post Operative Analgesic Efficacy of Intravenous Versus Rectal Acetaminophen & Opioid Requirement after Cleft Lip Surgery in Children - Muhammad Saleh Khaskhe*Ii, Raffia Tabassum, Bashir Ahmed Soomro, Sahib Gui,Riaz Hussain Sahito, Ramesh Kumar Tanwani , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: To compare analgesic efficacy of intravenous versus rectal acetaminophen and postoperative opioids requirement with either route for pain management after cleft lip repair. Study Design: Prospective interventional study. Place and duration: Department of Anaesthesia, Peoples university of Medical and Health Sciences Nawabshah, from January 2011 to December 2012. Material & Methods: 50 patients with American Society ofAnesthesiologist physical status I ( ASA I) of either sex, between 4 to 12 months of age further divided into two groups, 25 in each Group 1 (per rectal) and Group 2 (intravenous) scheduled for unilateral elective cleft lip repair at Paediatric surgery department received either intravenous or rectal acetaminophen after induction of anaesthesia. Intravenous group received 10mg/kg of acetaminophen and the rectal group received 30 meikg. After completion of surgery, patients were observed for pain at 1030,60,90,120,150,180,210 and 240 minutes postoperatively. FLACC pain and behavioural Score was adopted to assess the postoperative pain Results: Pain score of 4-6 requiring opioid supplement in Group I (per rectal) was observed twice in 6 (24%) patients and once only in 19 (76'14) patients, while in Group 2 (intravenous) twice in 7 (2$o/) patients and once only in 18 (72%) patients up to 240 in inutes postoperatively. Conclusion: Both intravenous and rectal routes of administration of acetaminophen are equally effective in terms of analgesia and reduce opioid supplements for breakthrough pain control and there is no difference in duration of analgesia with either route.